Patients treated with high‐dose intravenous immunoglobulin show selective activation of regulatory T cells. (4th July 2013) - Tjon, A. S. W.; Tha‐In, T.; Metselaar, H. J.; van, R.; van der, L. J. W.; Groothuismink, Z. M. A.; te, P. A. W.; van, P. M.; Kwekkeboom, J.
Summary Intravenous immunoglobulin (IVIg) is used to treat autoimmune and systemic inflammatory diseases caused by derailment of humoral and cellular immunity. In this study we investigated whether IVIg treatment can modulate regulatory T cells (Tregs) in humans in vivo. Blood was collected from IVIg‐treated patients with immunodeficiency or autoimmune disease who were treated with low‐dose (n = 12) or high‐dose (n = 15) IVIg before, immediately after and at 7 days after treatment. Percentages and activation status of circulating CD4+CD25+forkhead box protein 3 (FoxP3+) Tregs and of conventional CD4+FoxP3− T‐helper cells (Tconv) were measured. The suppressive capacity of Tregs purified from blood collected at the time‐points indicated was determined in an ex‐vivo assay. High‐dose, but not low‐dose, IVIg treatment enhanced the activation status of circulating Tregs, as shown by increased FoxP3 and human leucocyte antigen D‐related (HLA‐DR) expression, while numbers of circulating Tregs remained unchanged. The enhanced activation was sustained for at least 7 days after infusion, and the suppressive capacity of purified Tregs was increased from 41 to 70% at day 7 after IVIg treatment. The activation status of Tconv was not affected by IVIg. We conclude that high‐dose IVIg treatment activates Tregs selectively and enhances their suppressive function in humans in vivo. This effect may be one of the mechanisms by which IVIg restores imbalanced immune homeostasis in patients with autoimmune and systemic inflammatory disorders.